Dynamic economic emission dispatch considering renewable energy generation: A novel multi-objective optimization approach - Liu, Zhi-Feng; Li, Ling-Ling; Liu, Yu-Wei; Liu, Jia-Qi; Li, Heng-Yi; Shen, Qiang (Energy (Oxford), 2021)
This study contributes to construct the mathematical model of hybrid dynamic economic emission dispatch (HDEED) considering renewable energy generation and propose a novel solving approach based on enhanced moth-flame optimization algorithm. Renewable energy power generation technology has an important impact on reducing pollutant emissions and promoting sustainable development. Therefore, this study aims to investigate the HDEED problem in consideration of renewable energy generation and improve the economic and environmental benefits of the power system. First, a moth-flame optimization algorithm based on position disturbance updating strategy (MFO_PDU) was proposed aiming at the non-convex, non-linear and high-dimensional characteristics of HDEED problem. Second, the mathematical model of HDEED on the basis of Wind-Solar-Thermal integrated energy was constructed, while taking into account the valve point effect, equality constraints and inequality constraints. Finally, three cases including test systems of different scales were formulated and employed to verify the proposed approach, and the compromise solution was determined through membership function. The results revealed that the fuel cost obtained by the MFO_PDU algorithm was 11.31%, 4.01% and 5.27% smaller than those of HHO, TSA and MFO algorithms for small-scale test system. Accordingly, the research outcomes contribute in reducing the fuel cost and pollutant emissions of power generation system, and further improving the utilization and penetration rate of renewable energy. [Display omitted] •A hybrid dynamic economic emission dispatch model is formulated.•A novel MFO_PDU-based optimization strategy is proposed to solve HDEED problem.•The MFO_PDU-based approach can solve the HDEED problem efficiently.•The environmental and economic benefits of the power system are improved.